1976
DOI: 10.1080/15287397609529432
|View full text |Cite
|
Sign up to set email alerts
|

Consumer talcums and powders: Mineral and chemical characterization

Abstract: Representative consumer talcums and powders, including 20 body powders, baby powders, facial talcums, and also one pharmaceutical talc, were analyzed to determine their mineralogical and chemical composition. Where known, all were formulated prior to 1973. Of the 20 products 10 contained detectable amounts of tremolite and anthophyllite, principally asbestiform, while some also contained fragmented forms of these minerals. The amounts ranged from tenths of a percent to over 14% by weight; two contained detecta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
72
1

Year Published

1980
1980
2023
2023

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 127 publications
(73 citation statements)
references
References 32 publications
(33 reference statements)
0
72
1
Order By: Relevance
“…1 In 1976, talcum powder manufacturers instituted voluntary guidelines to prevent asbestos contamination in talc products, 24 but we did not find an increase in EOC risk with talc use on or before 1975; rather, we found that risk of EOC increased with use after 1975, which may be related to the recency of use. Harlow et al 24 observed ovarian cancer risk was increased in women using talc products before 1960, although Chang and Risch 22 found no relationship between risk and use either before or after 1970.…”
Section: Discussioncontrasting
confidence: 45%
See 1 more Smart Citation
“…1 In 1976, talcum powder manufacturers instituted voluntary guidelines to prevent asbestos contamination in talc products, 24 but we did not find an increase in EOC risk with talc use on or before 1975; rather, we found that risk of EOC increased with use after 1975, which may be related to the recency of use. Harlow et al 24 observed ovarian cancer risk was increased in women using talc products before 1960, although Chang and Risch 22 found no relationship between risk and use either before or after 1970.…”
Section: Discussioncontrasting
confidence: 45%
“…1 In animal studies, talc and other similar substances have been demonstrated to migrate from the vagina through the peritoneal cavity to the ovaries. 2 Henderson et al 3 also observed that particles with the appearance of talc were more prevalent in ovarian tumors than in normal ovarian tissue.…”
mentioning
confidence: 99%
“…The tremolite standard is from South Korea (Rohl et al, 1976). Scanning electron microscope energy-dispersive X-ray spectroscopy (SEM-EDXS) was used to obtain chemical analyses of amphibole samples, and identification was made on the basis of these data using the standard nomenclature (Leake, 1978) together with X-ray diffraction and optical data.…”
Section: Methods and Proceduresmentioning
confidence: 99%
“…In 1975, ore was being mined from approximately 6 of the 26 active stopes. Mining follows a typical cycle including: (1) blasting, which is done with gelatin dynamite and ammonium nitrate; (2) dissipation of dusts and gases; (3) removal of ore with some secondary blasting; and (4) drilling of blasting holes for the next shift.…”
Section: Miningmentioning
confidence: 99%
“…The term "talc" in the mineralogical sense denotes a specific rockforming mineral of the sheet silicate category; however, when "talc" is referenced in the industrial or commercial setting, it may represent a varied mixture of minerals with physical properties similar to the mineral talc (1). Minerals commonly found associated with talc include calcite, quartz, diopside, magnesite, serpentines (chrysotile, antigorite, and lizardite), and fibrous and nonfibrous amphiboles (tremolite, anthophyllite, actinolite) (1,2).…”
Section: Introductionmentioning
confidence: 99%